2013
DOI: 10.1007/s11064-013-1209-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Microglial Inflammation-Related and Brain-Enriched MicroRNAs Expressions in Response to In Vitro Oxygen–Glucose Deprivation

Abstract: Microglia plays important role in central nervous system immune surveillance and has emerged as an essential cellular component for understanding brain diseases. MicroRNAs (miRs) are small, noncoding RNAs that regulate the post-transcriptional expression of protein-coding mRNAs, which may have key roles in microglial activation in response to brain ischemia and other stressors. Primary cultured rat microglial cells were prepared, and then microglial activation model was established by oxygen-glucose deprivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
1
16
1
Order By: Relevance
“…Significant upregulation of miR‐124 was found in oxygen–glucose deprivation model (Kong et al. 2014). In our study, we did not detect a statistically significant change in the expression of miR‐124 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Significant upregulation of miR‐124 was found in oxygen–glucose deprivation model (Kong et al. 2014). In our study, we did not detect a statistically significant change in the expression of miR‐124 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work we found significant upregulation in these miRNAs expressions in the astrocytes stimulated with lipopolysaccharides (LPS) [28] and also in microglia exposed to oxygen glucose deprivation (OGD) [29]. Further experiments will need to prove if these miRNAs have a proinflammatory function or not in this animal model.…”
Section: Discussionmentioning
confidence: 92%
“…To date, our group has demonstrated the differential expressions of inflammation-related and brain-enriched miRNAs in activated glias [22,30] and MTLE rat model [14] . Next we have planned to modulate the expressions of some miRNAs in rat MTLE and meningitis models to discuss its potential as a therapeutic target for CNS diseases.…”
Section: Research Highlightmentioning
confidence: 99%
“…In our recent study entitled "Changes in Microglial Inflammation-related and Brain-enriched MiRNAs Expression in Response to In vitro Oxygen-Glucose Deprivation" [22] we used primary rat microglia cells OGD activated model and detected the expressions of the above 10 inflammation-related and brain-enriched miRNAs at different activated conditions. We found that the viability of the microglia was timedependent after OGD pretreatment.…”
Section: Research Highlightmentioning
confidence: 99%
See 1 more Smart Citation